KI-Textgeneratoren in der Wertschöpfungskette von Belletristikverlagen - Konstantina Thein (HTWK Leipzig - OA-Hochschulverlag, 2026)
This bachelor's thesis examines the role of AI text generators in fiction publishing. The aim is to explain how they work and identify potential applications in the value chain. Literature sources and expert interviews were used. The theoretical part comprises a market analysis and explanations of AI. In the empirical part, interviews were conducted with publishing representatives and readers in order to capture different perspectives. The results show that the use of AI text generators is possible at various stages of the value chain, but that there are challenges. Further research could focus on practical feasibility.